How Resilient are Lucid Motivators? Endeavoring Reforms for Effects of Psycho-social Factors on Workers Health Through Concurrent Engineering - Burcu Yılmaz Kaya; Elif Kılıç Delice (Elsevier, 2024)
Background: As the tremendous impact of extreme workloads, arduous working conditions, and disorganization disrupt humane job definitions in some industries, the need for workplace re-articulation was interfered to ameliorate psycho-social factors and suggest organizational intervention strategies. Especially for colossally wounded health-care (HC) systems, today it is now even more unrealizable to retain workforce resilience considering the immense impact of overwhelming working conditions. Methods: This study introduces employment of concurrent engineering tools to re-design humane workplaces annihilating abatement over devoured resources. The study handles HC-workforce resilience in a pioneering motive to introduce transformation of well-known motivators and proposes solutions for retention and resilience issues grounding on HC workers' own voice. Results: The proposed adjustable approach introduces integral use of focus group studies, SWARA, and QFD methods, and was practiced on a real-world case regarding Turkish HC workforce. The paper also presents widespread effects of findings by tendering generalized psycho-social rehabilitation strategies. Results confirmed the modifications of the most potent incessant motivators. Conclusion: "Burn out issues" and "Challenging work" were found as the most important motivator and satisfier, respectively, to be exigently fulfilled. Corrective interventions, required resolutions, and workplace articulation connotations were arbitrated in terms of entire outcomes on four dimensions in three different planning periods considering the current status, repercussions of pandemic, and contingency of similar catastrophes. Descriptive illustrations were additionally presented to support deducted interpretations.